Shakespeare's theater. - Hodges, C. Walter (Cyril Walter), 1909-2004.; Thaler, Alwin, 1891-; Encyclopaedia Britannica Films, inc. (Chicago : Encyclopaedia Britannica Films, 1961)
Covers the history of the English theater from its beginning through the Elizabethan and Jacobean eras, the design and construction of the Globe Theater and the production of plays in it.
1. Prologue to the Globe Theater.--2. The Playhouse comes to London.--3. The Globe Theater: its design and construction.--4. A day at the Globe Theater.
Mounted as 176 slides in 4 carousels.
Title on teacher's manual: The world of Shakespeare's theater by C. Walter Hodges.
Producer, Weldon Johnson; collaborator, Alwin Thaler; artist, C. Walter Hodges.
Keywords: Theater -- England -- History